1994
DOI: 10.1088/0963-0252/3/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Absolute fluorine atom concentrations in RIE and ECR CF4plasmas measured by actinometry

Abstract: We have measured the absolute fluorine atom concentrations in electron cyc!o!ron resonance (ECR! and reactive ion etching !ME) plasmas by optimizing the actinometry technique. The major difference between this work and conventional actinometry is that the Ar concentration measurements were pelformed by a residual gas analyser (RGA). The emission intensities of F (7037 A) and Ar (7504 A) were simultaneously measured by an optical multichannel analyser (OM) and the Ar concentration by a RGA. The F atom concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…RIE experiments were carried out with a Plasma Therm parallel plate etcher ͑Model 2484͒ operated with 700-1500 W of rf at 13.56 MHz, 37 mTorr, and flow rate ϭ20 sccm. Ion flux J i was measured with Langmuir probes, plasma potential with emissive probes and Langmuir probes, fluorine concentration by Ar actinometry, 15 and CF 2 concentration using diode laser infrared absorption. 16 Figure 1 gives a comparison of the measured SiO 2 etch rate by a CF 4 plasma, in the ECR 10 and RIE tools, with the etch rate given by Eq.…”
Section: ͑9͒mentioning
confidence: 99%
“…RIE experiments were carried out with a Plasma Therm parallel plate etcher ͑Model 2484͒ operated with 700-1500 W of rf at 13.56 MHz, 37 mTorr, and flow rate ϭ20 sccm. Ion flux J i was measured with Langmuir probes, plasma potential with emissive probes and Langmuir probes, fluorine concentration by Ar actinometry, 15 and CF 2 concentration using diode laser infrared absorption. 16 Figure 1 gives a comparison of the measured SiO 2 etch rate by a CF 4 plasma, in the ECR 10 and RIE tools, with the etch rate given by Eq.…”
Section: ͑9͒mentioning
confidence: 99%
“…It was found that the F concentration ranges from 10 21 to 10 22 m À3 , depending on the partial pressure of CF 4 and the input power density. This concentration is roughly two orders of magnitude higher than that found in low-pressure fluorine plasmas [15,16]. The other most abundant reactive species are CF 2 and CF 3 .…”
Section: Discussionmentioning
confidence: 63%
“…Comparison of model predictions to measured composition trends showed the wall-recombination probability for chlorine atoms on a chlorinated anodized-aluminum surface must exceed 0.1. Panon et al [59] have used actinometry [60] to establish the wall recombination probability as a function of the temperature of a Pyrex wall for O atoms flowing in a DC glow discharges for pressures ranging from 0.36-2 torr. Sarfaty et al have shown (see Fig.…”
Section: Modelingmentioning
confidence: 99%